Income redistribution and inequality in the Mexican tax-benefit system. (2017)
The paper examines the redistributive effect that was achieved by the Mexican taxbenefit system in 2014 using personal income tax, indirect taxes, social security contributions and social benefits. Our goal is to analyse the impact on inequality due to fiscal system action and then go further by demonstrating to what extent the contributions have on the total redistribution effect. The Mexican tax-benefit system is characterised by significant pre-fiscal income inequality. The contribution made by Vertical Equity (VE) is relatively important, but Horizontal Inequity (HI) reduces its impact. Income taxation does not greatly contribute to VE. Furthermore, some households receive unequal benefits, and therefore decrease the positive effect induced by VE.